2019
DOI: 10.1590/1806-9282.65.11.1384
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of ATRIA risk score for contrast-induced nephropathy after percutaneous coronary intervention for ST-segment elevation myocardial infarction

Abstract: SUMMARY BACKGROUND: The AnTicoagulation and Risk factors In Atrial fibrillation (ATRIA) risk score used to detect the thromboembolic and hemorrhagic risk in atrial fibrillation patients has been shown recently to predict poor clinical outcomes in patients with acute myocardial infarction (ACS), regardless of having atrial fibrillation (AF). We aimed to analyze the relationship between different risk scores and contrast-induced nephropathy (CIN) development in patients with ACS who underwent urgent percutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…8,23 Many different scoring systems and markers have been evaluated to predict the development of CIN. 8,28,29 Kelesoglu et al evaluated the relationship between CIN and SII in patients with non-STEMI 27 and reported that the risk of developing CIN was higher in patients with a high value of SII. In the present study, we also identified a relationship between the development of CIN and high SII in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…8,23 Many different scoring systems and markers have been evaluated to predict the development of CIN. 8,28,29 Kelesoglu et al evaluated the relationship between CIN and SII in patients with non-STEMI 27 and reported that the risk of developing CIN was higher in patients with a high value of SII. In the present study, we also identified a relationship between the development of CIN and high SII in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…The ATRIA scoring system is a simple and effective tool for easy risk stratification in different entities. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the present study showed that high scores may also be related to one-year mortality. Moreover, these scores were associated with contrast-induced nephropathy and poor coronary perfusion after primary percutaneous coronary intervention 13,14 . The CHA 2 DS 2 -VASc score, which was created from CHADS 2 , is recommended in contemporary guidelines for appraising oral anticoagulant therapy in patients with non-valvular AF 6 .…”
Section: Discussionmentioning
confidence: 99%